2016
DOI: 10.1111/ssqu.12249
|View full text |Cite
|
Sign up to set email alerts
|

The Terrorist Age‐Crime Curve: An Analysis of American Islamist Terrorist Offenders and Age‐Specific Propensity for Participation in Violent and Nonviolent Incidents

Abstract: Objective This study examines the age‐crime relationship among terrorist offenders. Method This study relies on a data set of over 600 American terrorism offenders inspired by one of three Islamist groups: Hamas, Hezbollah, or Al Qaeda. Results We find that the pattern of violent Islamist crime in the United States departs from the standard age‐crime curve in significant ways. Violent action among terrorist offenders peaks at a later age and occurs across a broader age range than is the case for ordinary viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…One possibility is that this trend relates to the general tendency for younger people to commit more violent acts (Farrington 1986) and is unrelated to identity fusion. Indeed, research has identified a wide range of biological and social factors that contribute to the association between age and violence, including physical strength, impulsivity, cognitive competence, freedom from supervision, and greater access to resources (Casey et al 2008;Fonagy 2003;Klausen et al 2016;Ulmer & Steffensmeier 2014). However, we propose that age may in fact interact with identity fusion effects through its relationship with identity development.…”
Section: Introductionmentioning
confidence: 76%
“…One possibility is that this trend relates to the general tendency for younger people to commit more violent acts (Farrington 1986) and is unrelated to identity fusion. Indeed, research has identified a wide range of biological and social factors that contribute to the association between age and violence, including physical strength, impulsivity, cognitive competence, freedom from supervision, and greater access to resources (Casey et al 2008;Fonagy 2003;Klausen et al 2016;Ulmer & Steffensmeier 2014). However, we propose that age may in fact interact with identity fusion effects through its relationship with identity development.…”
Section: Introductionmentioning
confidence: 76%
“…In fact, overall, terrorism is an adult, not a teen, crime. 28 We were able to assess with reasonable accuracy the age at which the offenders in our study were radicalized by subtracting the year of birth from the year of the first indication of behaviors consistent with militancy ( Figure 3). The results corroborated what other researchers have found: about two thirds of homegrown offenders were between the ages of 19 and 29 when they first exhibited signs of extremism.…”
Section: The Demographics Of "Homegrown" Jihadismmentioning
confidence: 83%
“…For example, Pfundmair et al 67 found radicalized individuals were significantly more likely to have a criminal record compared to non-radicals. Inconsistent findings were found regarding age, with Klausen et al 68 reporting that foreign fighters were significantly more likely to be younger; while Milla et al 69 found that age was positively associated with degree of endorsement of jihad (although this finding was not statistically significant). Nonetheless, it should be noted that most studies in this review included primarily male, Muslim, relatively young participants and the findings must be understood in the context of their samples rather than generalized to any young, male, Muslim individuals.…”
Section: Sociodemographic Characteristics As Risk Factors For Radicalisationmentioning
confidence: 97%